Сравнительно-кариологический анализ жаб рода Bufo (Amphibia, Anura) с территории Украины - Радченко, В.И.; Манило, В.В. (Вестник зоологии, 2009)
Исследованы кариотипы трех видов жаб фауны Украины: серой — Bufo bufo (Linnaeus, 1758), зеленой — Bufo viridis (Laurenti, 1768) и камышовой — Bufo calamita (Laurenti, 1768). Диплоидный набор всех трех видов состоит из 22 двуплечих хромосом, NF = 44. Различия между видами прослеживаются на уровне морфологии хромосом (у B. bufo — 10-я пара хромосом субметацентрик, остальные — метацентрики; у B. viridis — 4-я пара — субметацентрик, остальные — метацентрики; у B. calamita — 11-я пара — субтелоцентрик, остальные — метацентрики) и общей длины кариотипа (B. bufo — 115,5 мкм B. viridis — 102,8 мкм, B. calamita — 105,5 мкм). Вторичные перетяжки обнаружены у B. calamita на коротком плече 10-й пары и у B. bufo на длинном плече 5-й пары хромосом. Половые хромосомы не идентифицированы. Хромосомные формулы: B. bufo и B. viridis — 2n = 20V + 2sV = 22, NF = 44; B. calamita — 2n = 20V + 2sT = 22, NF = 44. Karyotipes of three species of toads Bufo bufo (Linnaeus, 1758), Bufo viridis (Laurenti, 1768) and Bufo calamita (Laurenti, 1768) from the fauna of Ukraine are examined: The diploid number consists of 22 chromosomes, NF = 44. Differences among these three species occur in the morphology of chromosomes (the 10-th pair of chromosomes in B. bufo has submetatsentrical structure, the others are metatsentrical; the 4-th pair of B. viridis is is submetatsentrical, whereas the others are metatsentrical; in B. ñalamita, the 11-th pair of chromosomes is subtelotsentrical, whereas the others are metotsentrical) and by general length of karyotipe: 115,5 μm for B. bufo, 102,8 μm for B. viridis, 105,5 μm for B. ñalamita. The secondary constrictions are found on the short shoulder of the 10-th pair in the B. calamita and on the long shoulder of 5-th pair of chromosomes in B. bufo. Sexual chromosomes are not identified. Chromosomal formulas of B. bufo and B. viridis are — 2n = 20V + 2sV = 22, NF = 44 and in B. calamita 2n = 20V + 2sT = 22, NF = 44.